Efek suplementasi kombinasi zat besi, vitamin C, dan asam folat terhadap peningkatan kadar hemoglobin dan kapasitas VO2 maks pada atlet sepak bola divisi utama dan satu nasional di Daerah Istimewa Yogyakarta - Zainal Abidin; Woro Woro; Mochammad Noerhadi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Excessive endurance exercise of football players may break their blood cells and decrease the level of haemoglobin (Hb). These will influence the aerobic capacity (VO2 max) and make the need for iron (Fe) of an athlete more than that of common people.Objective: To know the influence of Fe, vitamin C (ascorbic acid), and folic acid combined supplementation to the increase of VO2 max capacity of the national main and first division club football players in Daerah Istimewa Yogyakarta.Method: The study was RCT (Randomized Controlled Trial) experimental with a completely randomized design plan. The subjects were football players of Perserikatan Sepak Bola Indonesia Mataram (PSIM), Perserikatan Sepak Bola Sleman (PSS), and Perserikatan Sepak Bola Bantul (PERSIBA). They were then divided into two groups: treatment group and control group, each of them consisted of 35 players. Treatment group were given combined supplement capsules of 100 mg Fe, 100 mg vitamin C, and 2 mg folic acid three times a week for eight weeks, while the control group were given the placebo capsules. Before and after supplementation, their Hb and VO2 max were measured. However, the physical exercises were done based on the schedule, programmed by the clubs.Results: Combined supplementation of Fe, vitamin C, and folic acid could increase Hb level significantly (p=0.008), but there was no significant difference of VO2 max capacity between treatment group and control group (p=0.062). However, there was significant correlation between the increase of Hb level and VO max capacity (r=0.712; p<0.001).Conclusion: Combined supplementation of Fe, vitamin C, and folic acid led to the increase of Hb level of main and first division clubs football players in Daerah Istimewa Yogyakarta, but could not influence their VO2 max capacity.